Clinical Outcome in Cerebral Vasospasm Patients Treated with and without Intra-Arterial Nimodipine Infusion - Yindeedej, Vich; Nimmannitya, Pree; Noiphithak, Raywat; Punyarat, Prachya; Tantongtip, Dilok (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background Cerebral vasospasm (CV) after aneurysmal subarachnoid hemorrhage (aSAH) is still a problem. Hypertension, hypervolemia, and hemodilution (triple-H) therapy and oral nimodipine only a modest effect on patients. Intra-arterial treatment, including nimodipine, has been studied, but only as retrospective and single-arm prospective studies. We compared the outcomes between CV patients who received an adjunct intra-arterial nimodipine infusion (IANI) and those who received the standard medical treatment alone in a prospective randomized controlled trial.Methods In this study, patients between the age of 18 and 80 years, who underwent angiography within 14 days after aneurysm obliteration, were recruited and randomized to receive adjunct IANI or not, if they were identified with angiographic vasospasm. All the angiographic and neurologic data were recorded and analyzed during their admission, at the discharge date, and during the 6-month follow-up period.Results From June 2016 to December 2018, we enrolled 68 patients who were randomized into two groups, 36 in the intervention group and 32 in the control group. The patients' characteristics, aneurysm data, and modalities of treatment were similar between the two groups. Within 24 hours after IANI, Glasgow Coma Scale (GCS) score and motor strength revealed a significant improvement of 33.33 and 38.89%, respectively, in the intervention group versus 12.5 and 9.38%, respectively, in the control group. At discharge, the intervention group still had significant motor improvement (58.33 vs. 21.88%; p = 0.002).Conclusion IANI could be considered an effective treatment for CV without significant complications. This is the first RCT demonstrating statistically significant motor strength improvement within 24 hours and at discharge.
Keywords: intra-arterial nimodipine; subarachnoid hemorrhage; vasospasm; intracranial aneurysm